Prosaic conditions : Heinrich Heine and the spaces of Zionist literature - Rokem, Na'ama. (Evanston, Illinois : Northwestern University Press, 2013)
In this book, the author observes that prose writing -- more than poetry, drama, or other genres -- came to signify a historic rift that resulted in loss and disenchantment. The author treats prose as a signifying practice -- that is, a practice that creates meaning. During the nineteenth and twentieth centuries, prose emerges in competition with other existing practices, specifically, the practice of performance. Using Zionist literature as a test case, the author examines the ways in which Zionist authors put prose to use, both as a concept and as a literary mode. Writing prose enables these authors to grapple with historical, political, and spatial transformations and to understand the interrelatedness of all of these changes.
Prose regnant : world, state, and subject in Hegel's lectures on aesthetics -- Heinrich Heine, explorer of the current prosaic condition -- Mediated situatedness in the reception of Heinrich Heine -- Theodor Herzl's technocratic world-making in prose -- Haim Nahman Bialik's icy river of prose -- Heine and the Israeli novel -- Conclusion.
Revision of the author's thesis (PhD)--Stanford University, 2007.
Includes bibliographical references (pages [159]-211) and index.
Print version record.
English.
JSTOR
Keywords: Bialik, Hayyim Nahman, -- 1873-1934 -- Criticism and interpretation; Herzl, Theodor, -- 1860-1904 -- Criticism and interpretation; Heine, Heinrich, -- 1797-1856 -- Criticism and interpretation; Hegel, Georg Wilhelm Friedrich, -- 1770-1831 -- Criticism and interpretation; Bialik, Hayyim Nahman, -- 1873-1934; Hegel, Georg Wilhelm Friedrich, -- 1770-1831; Heine, Heinrich, -- 1797-1856; Herzl, Theodor, -- 1860-1904; Zionism in literature; Prose literature -- Jewish authors -- History and criticism; Prose -- Auteurs juifs -- Histoire et critique; LITERARY CRITICISM -- General; Zionism in literature; Languages & Literatures; Literature - General; Criticism, interpretation, etc